GANGGUAN TINGKAH LAKU PADA ANAK - Rehani rehani (Institut Agama Islam Negeri Imam Bonjol Padang, 2012)
Mental disorder is a repetitive and persistent pattern that violated human’s rignt and social norms. There are some type of mental disorder such as aggression to people and animal, destruction of property, deceitfulness or theft and serious violations of rules, and other serious violations of rules.